Rehabilitation of Hydropower : An Introduction to Economic and Technical Issues - Goldberg, Joseph (World Bank, Washington, DC, 2014)
Section one provides a concise summary of the results of the study and includes an overview of the conclusions as well as lessons learned based on the assessment of the case studies. Section two gives the context for the study including the definition of a set of hydroelectric project development options as background to related discussions of rehabilitation later in the report. Section three provides an overview of the contents of this report. Section four discusses the development and application of an assessment tool to facilitate the rapid assessment of regional hydropower inventories. This assessment tool has been applied to a data base and inventory of generating station information in the African and Central American regions to identify possible candidates for rehabilitation. The characteristics of the two inventories are outlined in the section and details of the approach and the results of the application of the tool to the two regions are given in annex A. Section five presents a screening-level economic assessment model which quantifies potential costs and benefits associated with hydropower rehabilitation, concluding with generally accepted economic parameters. Details of the development of the economic model are given in annex B. Section six summarizes the application of the economic model to the two data base and inventory of generating station information for the two regions (Africa and Central America). The application of the economic model is not intended to provide site-specific economic parameters for each station since there is insufficient information in the data base for this. The objective of modeling is to provide an order-of magnitude market assessment of the potential for rehabilitation based on the limited data available in the data base. Section seven presents a summary of the important elements of a number of case studies involving historical rehabilitation and expansion projects. The section is the source of a list of overall lessons learned which is presented in the conclusions section. Section eight is a summary of issues which covers the spectrum of Incentives to Barriers associated with the rehabilitation of hydro projects under three broad categories: technical, financial, and environmental or institutional.